Math, asked by ramjim711, 5 months ago

(1) Solve the equation
3x-12
= 30 - 2x
4​

Answers

Answered by buttercup25
1

Answer:

Simplifying

3x + -12 = 30

Reorder the terms:

-12 + 3x = 30

Solving

-12 + 3x = 30

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.

-12 + 12 + 3x = 30 + 12

Combine like terms: -12 + 12 = 0

0 + 3x = 30 + 12

3x = 30 + 12

Combine like terms: 30 + 12 = 42

3x = 42

Divide each side by '3'.

x = 14

Simplifying

x = 14

Answered by atiba83
0

Step-by-step explanation:

-36-22

=58

hope it helps

Similar questions